Planar six-element ultra wideband array for target detection - Kasi B.; Chakrabarty C.K. (Maxwell Science Publications, 2023)
This study presents a planar Ultra-Wide Band (UWB) antenna array based on six identical UWB antenna elements. The feed network for the proposed structure is realized with Wilkinson power dividers. Dolph-Chebyshev distribution has been used to provide tapered feeding for the radiating elements. The fabricated array, with a compact size of 200 90 mm2, operates over the frequency band from 3.8 to 10 GHz with a return loss less than -10 dB. Moreover, the measured peak gains of the array range from 5.5 to 10.8 dBi against the frequency. The experimented and simulated results are in good agreement. A time domain study has been performed to assess the suitability of the designed array for UWB applications. Maxwell Scientific Organization, 2013.